Evaluation of silage crop and dietary crude protein levels for beef cattle and selection of Lactobacillus buchneri from corn silage for use as inoculant - Silva, Leandro Diego da (2016)
Chapter 1 - Two trials were conducted to evaluate the effects of silage crop and levels of dietary crude protein (CP) in Nellore beef cattle. The experimental diets consisted of Stylosanthes (StS) or corn silage (CS) with two levels of dietary CP, 110 and 130 g CP/kg diet on dry matter (DM) basis. The forage to concentrate ratio was 50:50 on a DM basis. In Experiment 1, four bulls were used, with an average initial body weight (BW) of 450 ± 37.9 kg, surgically cannulated in the rumen and abomasum. The bulls were assigned to a 4 × 4 Latin square with a 2 × 2 factorial design of treatments, and four 16-day periods. In this experiment, we collected ruminal fluid, abomasal digesta, feces, urine, and blood. In addition, the kinetic parameters of DM, CP and neutral detergent fiber (NDF) degradation were estimated. In Experiment 2, 40 bulls with an average initial BW of 374 ± 16.5 kg were distributed into a 2 × 2 factorial in a randomized design with ten replicates. The trial lasted 99 days and was divided into a 15-day period for adaptation and an 84-day period for data collection. The intake and digestibility of nutrients, as well as animal performance were evaluated in Experiment 2. The potentially degradable fractions of DM, CP, and NDF of StS were lower than CS (P<0.004). The diets containing StS showed lower ruminal digestibility of organic matter (OM) and lower total digestibility of OM, CP, and NDF than diets containing CS (P<0.050). The StS-based diets showed higher values for ruminal pH in comparison with CS-based diets (P=0.010). The ruminal NH 3 -N concentration was higher for the level of 130 g CP/kg diet in comparison with 110 g CP/kg diet (P<0.001). The dietary CP level affected urea nitrogen in blood (P<0.001) and urine (P=0.017), which in the diets containing StS and CS were higher at the level of 130 g CP/kg diet. The diets containing StS showed higher intake of DM, OM, CP, NDF, and indigestible neutral detergent fiber (iNDF) than diets containing CS (P<0.008). However, the amount of digested nutrients (kg/d) was similar between treatments (P>0.050). The silage crop and dietary CP levels had no effect on productive performance (P>0.050), but the StS-based diet tended to decrease feed efficiency (P=0.085). Thus, StS, as well as the level of 110 g CP/kg diet, can be used to feed finishing beef cattle. Chapter 2 - One hundred and fifty-one LAB strains were isolated from whole-plant corn silage in tropical weather. Their identifications were based on sequence analysis of 16S rDNA. The predominant species were Lactobacillus plantarum 53.0%, Pediococcus pentosaceus 11.9%, Lactobacillus buchneri 9.9%, Lactobacillus pentosus 5.3%, Weissella cibaria 4.6%, and Lactobacillus brevis 4.0%. Lactobacillus buchneri strains were predominant at day 56 of ensiling. Eight L. buchneri strains from a total of 15 were preselected, based on growth rate and metabolites production. The strains selected were evaluated on fermentation and aerobic stability of corn and sugarcane silages, four strains in each crop. There was no improvement of the inoculation with the strains 56.22, 56.27, 56.28, and 56.29 on the DM content, yeast and molds population, DM losses, and aerobic stability of corn silage (P > 0.050). Inoculated silages had lower concentration of acetic acid and higher ethanol in comparison with the control silage (P < 0.050). While the strains 56.1, 56.4, and 40788 showed highest DM content, and lowest DM losses when applied in sugarcane silage. At day 90 of ensiling, the commercial strain showed lowest population of yeasts and molds in sugarcane silage. However, the aerobic stability was not affected. After air exposure, all silages deteriorate and had high population of yeast and molds. Preselection of L. buchneri strains based on acetic acid production showed the best results on silage fermentation. Thus, the strains 56.1 and 56.4 are promising for use as an inoculant in sugarcane silages.